Sistema de classificação dos solos baseado na estrutura do espaço poroso - Ottoni, Marta Vasconcelos (2017)
We propose a soil classification system named SPSCS (Soil Pore spaceStructural Classification System), which is based on pore space structure and takes into account the water retention curve. SPSCS was designed according to the textural classification system and it conceives a structural triangle equivalent to the textural triangle. Nine Orders and four Suborders were proposed, resulting in 36 structural Families that group soils with similar air availability curves (Aa). Aa is understood as the complement of the water retention curve in relation to the saturated water content. The soil classification methodology took into consideration a parameterization of the van Genuchten equation for Aa. Simultaneously, we conceived a hydrophysical database for Brazilian soils as a support to the proposed methodological approach, allowing also the development of studies on pedotransfer functions for hydraulic properties involving tropical and temperate regions. In the context of SPSCS, we revealed a clear pattern of similarity among Aa curves within Families. The system was successfully implemented in an extensive and diversified soil database compiled in the study, where all soil Orders and most Families were represented. The study of the relationship between the soil classification system and soil characteristics in the database led to the conclusion that the SPSCS was able to confirm soil structural differences or similarities from analogue or distinct pedological and textural classes. Such is the case of clayey Ferralsols grouped in the same structural Families of sandy soils, among other evaluated cases. In conclusion, SPSCS is a promising tool in hydropedological studies and in the development of pedotransfer functions of hydraulic properties.